Innovation in Hospitality Education Anticipating the Educational Needs of a Changing Profession (Innovation and Change in Professional Education,, 2018)
This book analyses the development of hospitality education from vocational to higher education, and discusses the positioning of hotel schools. It addresses questions such as: Should hospitality management become part of generic business education? Are the technical training programmes that have defined the identity of these schools a remnant of their vocational past, or have they contributed to the successful careers of many hospitality graduates? Topics discussed in the book are curriculum innovation, the theory of experimentation, the nature of hospitable behaviour, information technology, life-long learning and developments for future curricula. The book makes clear that the debate on the balance between theory and practice will not only define the future of hospitality management education, but can also be considered a relevant case study in other business disciplines. The history of hospitality education goes back to the end of the nineteenth and early twentieth century when hotel schools were founded to train the protocol and technical skills required to receive the travellers of those days. Since then, the scale and complexity of the hospitality industry and its professions have changed, as well as our understanding of what makes a business -whether it offers accommodation or something else- "hospitable". The scope and educational level of hotel schools have evolved accordingly, and hospitality management has become a popular discipline in the traditional and renowned hotel schools as well as in universities. .